1990
DOI: 10.1002/ajmg.1320350102
|View full text |Cite
|
Sign up to set email alerts
|

Dermatoglyphic analysis of autistic Basque children

Abstract: We have analyzed the digital and palmar dermatoglyphics in a sample of autistic children from the Basque Country. The results have been compared with those from a control sample having the same characteristics relative to the ethnic region. We found significant differences between the digital dermatoglyphics of autistic boys and control boys. Autistic children have a higher frequency of transitional radial loops and a lower frequency of dicentric whorls; also the total finger ridge count (TFRC) and radial coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…In addition to this research we certainly have to add the results that were obtained by Arrieta et al 19 , which also confirmed that autistic children have a lower TRC and a wider atd angle, so, it is concluded that the obtained results do not contradict the hypothesis that genetic factors might be significant in etiology of unknown origin autism.…”
Section: Discussionsupporting
confidence: 77%
“…In addition to this research we certainly have to add the results that were obtained by Arrieta et al 19 , which also confirmed that autistic children have a lower TRC and a wider atd angle, so, it is concluded that the obtained results do not contradict the hypothesis that genetic factors might be significant in etiology of unknown origin autism.…”
Section: Discussionsupporting
confidence: 77%
“…Not all studies, however, agree on this finding [ 34 ]. Arrieta and colleagues [ 35 ] found larger atd-angles in girls with ASD than in boys. A few descriptions of dermatoglyphic variables in people with ASD in Eastern European countries (Croatia, Romania, and Serbia) have recently become available.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][14][15]. Dermatoglyphics patterns are reported to be markers for certain genetic disorders like Down's syndrome [16,17], autism, [18] and skeletal malformations such as polydactyly [3]. It is also useful in psychiatry [19] and in the diagnosis of Schizophrenia and other medical conditions such as cardiovascular diseases, diabetes mellitus type II, epilepsy, hypertension [20][21][22][23], Kanner's syndrome [22,24], hypoparathyroidism, [3,25,26], Klinefelter's syndrome [27] as well as in dentistry [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%